14th IEEE International Conference on Nanotechnology 2014
DOI: 10.1109/nano.2014.6968108
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of cylindrical micro-components using laser scan lithography and electrolytic etching of stainless steel pipes

Abstract: A new fabrication method of cylindrical microcomponents was investigated using laser scan lithography and electrolytic etching. First, net-like patterns were formed by repeating delineations of helical patterns crossing each other on fine pipes of stainless steel with an outer diameter of 100 μm and a wall thickness of 20 μm. The pipes were coated with 4-μm thick negative resist, and four couples of helical patterns were delineated for making the net-like patterns. Next, the pipes were etched in an aqueous ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As another type of exposure system for patterning on cylindrical specimens, laser-scan delineating systems have already been developed. [27][28][29][30][31] However, a long time is required for delineating complicated patterns in large fields because the laser beam must be scanned serially. In comparison, in the case of the new exposure system, the exposure time is almost constant and does not depend on the complexity of the patterns.…”
Section: Introductionmentioning
confidence: 99%
“…As another type of exposure system for patterning on cylindrical specimens, laser-scan delineating systems have already been developed. [27][28][29][30][31] However, a long time is required for delineating complicated patterns in large fields because the laser beam must be scanned serially. In comparison, in the case of the new exposure system, the exposure time is almost constant and does not depend on the complexity of the patterns.…”
Section: Introductionmentioning
confidence: 99%
“…To answer the requirement, various researches on developing lithography systems for replicating or delineating patterns on cylindrical materials were carried out [1][2][3][4][5][6][7]. The authors also developed laser-scan exposure systems onto fine wires and pipes with diameters of 40-500 µm [8][9][10][11][12][13]. It was demonstrated that very precise patterns were arbitrarily delineated on surfaces of such very fine cylindrical materials.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that very precise patterns were arbitrarily delineated on surfaces of such very fine cylindrical materials. In addition, fabrication processes of fine cylindrical micro-components such as coil springs and pipes with multi-holes were also developed [8][9][10][11] [13].…”
Section: Introductionmentioning
confidence: 99%